Smallholder maize farmers' food consumption expenditures in Ghana: The mediating role of commercialization - Asante, S.B.; Osei-Asare, Y.B.; Kuwornu, J.K.M. (Faculty of Economics and Management, 2016)
This paper examines the effect of smallholder maize farmers' commercialization on their household food consumption expenditures in Ghana using data from the Ghana Living Standard Survey Round Five (GLSS5). The results indicate that the intensity of smallholder maize commercialization is generally low and that better output price, quantity of maize produced, farm size, type of market or point of sale, access to mobile phone network coverage, proportion of crops given to landlord, instant payment for maize sold, are inter alia key incentive variables that influence the intensity of maize commercialization. The study also revealed that intensity of maize commercialization positively influenced food consumption expenditures. Increases in the sale of maize results in increases in purchases of food items needed to address household food security needs. These findings demonstrate the urgent need to strengthen smallholder market integration initiatives, encourage market information delivery systems, and establish more retail outlets with improved market facilities in order to promote production and trade in high value cereals such as maize in Ghana.
Keywords: Commercialization; Consumption; Food expenditures; Households; Smallholder maize farmers